In situ observation of short fatigue crack propagation in oxygenated water at elevated temperature and pressure - Duff, J; Marrow, T (Elsevier, 2013)
A new method is demonstrated for in situ measurement of short crack propagation rates during a corrosion fatigue test of an austenitic stainless steel within a windowed autoclave at 250 degrees C, 50 atmospheres, oxygenated water. Digital image correlation is used to monitor crack growth through measurement of the opening displacements of defects; either focused ion beam (FIB) milled notches from which fatigue cracks initiated, or stress corrosion cracks that subsequently propagated by fatigue. Copyright 2012 Elsevier Ltd.